Conceptions and misconceptions about computer science in preschool teachers - Weimer, Nahuel José Nicolás; Santos, Jorge Alejandro; Medrano, Gustavo; Schinca, Hernán; Hermida, María Julia (Asociación Argentina de Ciencias del Comportamiento (AACC), 2024)
Introduction: Computer science (CS) was recently incorporated as core knowledge in Early Childhood Education and is mostly taught by class teachers. However, we do not know how much teachers know about basic CS concepts they should teach. Objectives: This study analyses the conceptions of the preschool teaching staff about CS. Specifically, we addressed the prevalence of misconceptions about CS and whether that prevalence is associated with sociodemographic variables (i.e., teacher’s age, years of expertise, maximum educational level reached or CS training). Methodology: An anonymous online survey (n= 223) was conducted between April and July 2022, among preschool teachers in Buenos Aires, Argentina, addressing the aspects suggested by previous studies and by CS experts as being the most confusing for a non-expert audience. Percentages of each concept are described. Logistic regression analyses were conducted to check whether sociodemographic variables predicted correct responses by item. Results: Overall, the majority (sixteen out of the twenty-three) of the sentences were correctly answered (i.e., as the interviewed computer scientists had answered). However, the technical aspects of CS are highly unknown. No sociodemographic variable predicted the probability of giving a correct answer. Discussion: Technical issues of CS should be addressed by courses. Instead, aspects linked to the learning of CS are mostly known.
Trabajo presentado en la XIX Reunión Nacional y VIII Encuentro Internacional de la Asociación Argentina de Ciencias del Comportamiento (AACC), realizado del 30 de agosto al 1 de septiembre de 2023 en la Ciudad Autónoma de Buenos Aires, Argentina.
Keywords: Ciencias sociales::Ciencias de la educación